1991
DOI: 10.1080/01411599108203437
|View full text |Cite
|
Sign up to set email alerts
|

Linear birefringence studies of incommensurate systems: II. KFeF4

Abstract: The temperature dependence of the linear birefringence (LB), Anc, is measured in the range 5 K 5 T 5 500 K on samples of KFeF,, which originate from hydrothermal, flux and Bridgman growth techniques.Pronounced anomalies are found at the orthorhombic-orthorhomic phase transition at r, -400 K. It is weakly discontinuous with a near-tricritical exponent p -0.2. Weak anomalies near -T, + (25.. .40 K) seem to indicate a transition into anjntermediate incommensurate phase. Its XY-model character is reflected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This is consistent with the fact that the coexistence of two ordered phases is not clearly proved. Therefore, we can suppose the coexistence of partially disordered phases, or following Bianchi and Saint Grégoire [4,11], the presence of an intermediate modulated phase between phase II and phase III. However, satellite reflections characteristic of the incommensurable phase have never been observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the fact that the coexistence of two ordered phases is not clearly proved. Therefore, we can suppose the coexistence of partially disordered phases, or following Bianchi and Saint Grégoire [4,11], the presence of an intermediate modulated phase between phase II and phase III. However, satellite reflections characteristic of the incommensurable phase have never been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in the KFeF 4 isotype compound have shown that the mechanisms of the phase transition are complex. Indeed, according to Bianchi et al [4] an intermediate modulated phase between the phase II and the phase III is possible. Furthermore, the recent studies on this latter compound have shown that the phase transition II → III is quasi-continuous or it is weak to first order [5].…”
Section: Introductionmentioning
confidence: 99%